Effect of hot air and infrared roasting on hazelnut allergenicity. (16th April 2021) - Lamberti, Cristina; Nebbia, Stefano; Antoniazzi, Sara; Cirrincione, Simona; Marengo, Emilio; Manfredi, Marcello; Smorgon, Denis; Monti, Giovanna; Faccio, Antonella; Giuffrida, Maria Gabriella; Balestrini, Raffaella; Cavallarin, Laura
Highlights: Roasting at 170 °C reduced hazelnut immunoreactivity, regardless of the method. Infrared roasting at 170 °C decrease hazelnut immunoreactivity. Roasting caused a loss of lipids compartmentalization. Roasting caused an alteration of the structure of the protein bodies. Abstract: Roasting is known to affect the protein profile and allergenicity of hazelnuts ( Corylus avellana cv TGL). The aim of the study was to investigate whether roasting techniques based on different heat transfer methods (hot air and infrared), differently affect the protein solubility and the IgE-binding capacities of both the soluble and insoluble hazelnut protein fractions. The immune-reactivity of the Cor a 9, Cor a 11 and Cor a 14 allergens resulted to be stable after roasting at 140 °C, for both types of treatment, while roasting at 170 °C caused a reduction in IgE-binding, which was particularly noticeable after infrared processing, that led to an almost complete disappearance of allergenicity. Microscopical analyses showed that roasting caused cytoplasmic network disruption, with a loss of lipid compartmentalization, as well as an alteration of the structure of the protein bodies and of the cell wall organization.